Study of titanium, tantalum and chromium catalysts for use in industrial transformations - Tau, Prudence Lerato (Rhodes University, Faculty of Science, Department of Chemistry, 2007)
PART A The syntheses, spectroscopic and electrochemical characterisation of a series of titanium and tantalum phthalocyanine complexes are reported. The complexes are unsubstituted and substituted at either the peripheral or non-peripheral positions with sulphonates, aryloxy, arylthio or amino groups. The complexes mostly exhibit Qbands in the near-infrared region as well as interesting properties in different solvents. The interaction of differently sulphonated titanium and tantalum phthalocyanine complexes with methyl viologen (MV[superscript 2+]), and hence the stoichiometry and association constants are evaluated. Detailed photophysicochemical properties of the complexes were investigated and are for the first time presented with fluorescence lifetimes easily obtained from fluorescence quenching studies. The transformation of 1-hexene photocatalysed by aryloxy- and arylthio-appended complexes is also presented for the first time. The electrochemical properties of the complexes are unknown and are thus presented. Cyclic (CV) and square wave (SWV) voltammetries, chronocoulometry and spectroelectrochemistry are employed in the study of the complexes. Two oneelectron reductions and a simultaneous 4-electron reduction are observed for the unsubstituted Cl[subscript 3]TaPc. Reduction occurs first at the metal followed by ring-based processes. The tetra- and octa-substituted derivatives however exhibit peculiar electrochemical behaviour where a multi-electron transfer process occurs for complexes bearing certain substituents. For all complexes, the first two reductions are metal-based followed by ring-based processes. A comparative study of the electrocatalytic activities of the complexes towards the oxidation of nitrite is also investigated. The complexes are immobilised onto a glassy carbon electrode either by drop-dry or electropolymerisation methods. All the modified electrodes exhibit improved electrocatalytic oxidation of nitrite than the unmodified electrodes by a twoelectron mechanism producing nitrate ions. Catalytic currents are enhanced and nitrite overpotential reduced to ~ 0.60 V. Kinetic parameters are determined for all complexes and a mechanism is proposed. PART B: The syntheses and electrochemical characterisation of chromium and titanium complexes for the selective trimerisation of ethylene to 1-hexene are presented. The synthesis of the chromium complex requires simple steps while tedious steps are used for the air-sensitive titanium complex. The spectroscopic interaction of the chromium complex with the co-catalyst methylaluminoxane is investigated. The complexes are characterised by electrochemical methods such as cyclic voltammetry and spectroelectrochemistry.
Keywords: Titanium; Tantalum; Phthalocyanines; Electrochemistry; Photochemotherapy; Chromium; Spectrum analysis